Análise de indicadores de desenvolvimento sustentável em Moçambique: uma aplicação do barômetro da sustentabilidade - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2017)
In recent years it has develop methods for assessing the progress towards the sustainable development (SD) at the national, regional, or local scale through Sustainable Development Indicators (SDI). The importance of the use of this tool for the implementation of public policies, based on the SD, was held at the United Nations Conference on Environment and Development in Rio de Janeiro in 1992. Although they are very important in the evaluation process, these tools are currently little known and its use has not been well done. In Mozambique, the application of tools for sustainability analysis in its several dimensions was not performed properly due to lack of data on indicators, methodologies and especially the absence of a solid institutional structure to monitor effectively the implementation of the Environmental Strategy for the Sustainable Development of Mozambique. In this context, this research aims to analyze the level of sustainable development of Mozambique, in the period of 2001 and 2014, by applying the Barometer of Sustainability (BS). The BS is a two-dimensional analysis method that encloud two subsystems: the human and the environment. From them are calculated synthetic indexes called "environmental well-being index and "human welfare index”. The research is bibliographical and documental and 40 indicators were selected and defined performance ranges for each indicator. The result shows that Mozambique is on a performance or Potentially Unsustainable condition in 2014 compared to the Unsustainable condition in 2001.
Keywords: Barômetro de Sustentabilidade; Indicadores de Desenvolvimento Sustentável; Moçambique; CNPQ::CIENCIAS BIOLOGICAS